2016
DOI: 10.1039/c6cc04811k
|View full text |Cite
|
Sign up to set email alerts
|

Separation of carbon dioxide from flue gas by mixed matrix membranes using dual phase microporous polymeric constituents

Abstract: This study presents the fabrication of a new mixed matrix membrane using two microporous polymers: a polymer of intrinsic microporosity PIM-1 and a benzimidazole linked polymer, BILP-101, and their CO separation properties from post-combustion flue gas. 17, 30 and 40 wt% loadings of BILP-101 into PIM-1 were tested, resulting in mechanically stable films showing very good interfacial interaction due to the inherent H-bonding capability of the constituent materials. Gas transport studies showed that BILP-101/PIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…As for MOFs, microporous polymers have been grown from functionalized surfaces to generate thin films [51][52][53] or mixed with other polymers to create mixed membranes. 54,55 However, if these techniques can be converted into a feasible technology is so far questionable. Again, in this respect some microporous polymers exhibit unique features, which make their technologically relevant processing possible.…”
Section: 47mentioning
confidence: 99%
“…As for MOFs, microporous polymers have been grown from functionalized surfaces to generate thin films [51][52][53] or mixed with other polymers to create mixed membranes. 54,55 However, if these techniques can be converted into a feasible technology is so far questionable. Again, in this respect some microporous polymers exhibit unique features, which make their technologically relevant processing possible.…”
Section: 47mentioning
confidence: 99%
“…Ali et al incorporated BILP in PIM-1 MMMs and observed significant improvement in permeability of CO 2 with slight decrease in CO 2 /N 2 selectivity up to 30 wt.% loading. 128 Further increase in loading to 40 wt.% resulted in decrease in CO 2 permeability and enhancement in CO 2 /N 2 selectivity. The authors claimed that initial improvements in the permeability are due to increase in interfacial void formation with BILP loading.…”
Section: Carbon-based MMMmentioning
confidence: 97%
“…PIM-1/BILP membrane tested in real flue gas conditions showed stable separation performance. 128 The nanoparticles are used to fabricate MMMs and separation performance is strongly affected by polymer chains-nanoparticles interactions as well as nanoparticles-penetrants interactions. These interactions may induce the free volume between the polymer chains resulting in enhancement in gas diffusion.…”
Section: Carbon-based MMMmentioning
confidence: 99%
“…Both studies indicated that tailoring the pore surfaces with functionalities brought benefits in CO 2 capture from postcombustion gases. The practices of introducing CO 2 ‐philic groups (e.g., OH, COOH, NH 2 ) onto the pore walls of microporous organic membranes were extensively executed by our researchers …”
Section: Gas Separation With Microporous Organic Membranesmentioning
confidence: 99%
“…The method of pore modulation to improve CO 2 capture efficiency was extended to other microporous organic membranes including crystalline 2D and amorphous 3D ones, the work of which is summarized in Figure . Based on the survey, it can be concluded that introduced surface functionality and small pores contribute significantly to increasing the selectivity, and fully interconnected pores (equivalently by high surface areas) bring a huge enhancement in gas permeability.…”
Section: Gas Separation With Microporous Organic Membranesmentioning
confidence: 99%